Analysis of Impact of Cremation on Water Quality of River Ganga at Digha Ghat in Patna, Bihar, India - Anand, Akshay; Kumar, Amit; Kumar, Jayant; Singh, Bihari; Gangwar, Tripti (International Journal of Environmental Sciences, 2024)
Purpose: Water related ecosystems face numerous threats, including pollution, climate change and overexploitation. The extent of surface water bodies, such as lakes, rivers and reservoirs, are rapidly changing worldwide. Traditional belief holds that being cremated at the bank of Ganga River and immersing ashes cleans the sins of those who die and carry them directly to salvation. Cremation remains when combine with river water, directly or indirectly impact human health and harms aquatic life. The present study was carried out at cremation ground on the river Ganga at three sampling sites near Digha Ghat in Patna district of Bihar, India. The objective of the study was to investigate water quality and suitability of water of Ganga River for aquatic life, irrigation and drinking. Methodology: Total twelve physiochemical parameters viz temperature, TDS, pH, turbidity, electrical conductivity, total hardness, calcium hardness, magnesium hardness, DO, BOD, alkalinity, acidity, chloride, fluoride, phosphates, sulphates, sodium, potassium, iron were analysed by using standard methods described by APHA and the results were compared with water quality standards prescribed by Bureau of Indian standard (IS:10500). Findings: The abundance of major ions trends indicating impacts of cremation activities on river water quality. Parameters, DO, BOD and phosphates were not recorded within permissible limit in water samples collected from cremation ground at Digha ghat. Higher values of turbidity at locations near cremation ghat may be attributed to addition of ashes bathing and other anthropogenic activities. Unique Contribution to Theory, Practice and Policy: The study suggests that deterioration of water quality at cremation ghat of river Ganga needs regular monitoring and conservation measures.